APPLICATION OF ADMINISTRATIVE PAYMENT OF STUDENTS IN SCHOOL SD Kwitang IV PSKD USING MICROSOFT programming language Visual Foxpro 9.0 - Yosiana Octavianita; Syahril Syahril (Jurnal Sistem Informasi, 2010)
Advances in technology today, making individuals or organizations keptthinking to be able to develop knowledge and expertise in all fields. Without theawareness, development of technology that very rapid progress in terms ofsoftware and hardware. Especially in the field of computers, applicationssoftware development more and more popping up. With the participation andinnovation are more advanced and of course supported by a computer, anyindividual or organization can create an application using the software that hasbeen widely known by computer users in particular and society in general.Process with the use of computers known as computerization. Computerizedalmost required for every individual or a intansi including intansi in education,in order to obtain information faster and more accurate in terms of making adecision. In the world of Education student administration strongly support thepayment process the school's performance, particularly private schools whereeach school activities and the income derived from payment of studentadministration, payable monthly. Therefore a good idea every income andexpenditure broken down properly and accurately, but currently lack thefacilities to facilitate the processing of each student and the administration basedon results obtained by the authors of the observations to several elementaryschools located in the area of South Jakarta, on average, from elementary schoolThe students used to process data manually, such as hand writing on a book, topancatatan in payment of school administration, even in filling the biodata ofstudents, something similaris often used